Ignorance, intention and stochastic outcomes☆ - Friedrichsen, Jana; Momsen, Katharina; Piasenti, Stefano (Journal of behavioral and experimental economics, 2022)
In sequential interactions, both the agent’s intention and the outcome of his choice may influence the principal’s action. While outcomes are typically observable, intentions are more likely to be hidden, leaving potential wiggle room for the principal when deciding on a reciprocating action. We employ a controlled experiment to investigate how intentions and outcome affect the principal’s actions and whether principals use hidden information as an excuse to behave more selfishly. We find that principals react mainly to the intention of the agent. When intentions are not revealed by default, principals tend to select into information based on their inclination to behave more prosocially. While information avoidance is frequent and selfishness is higher with hidden information, we do not find evidence of a strategic exploitation of moral wiggle room.